Productive management proposal to increase the level of efficiency of the food sector through the application of Lean Manufacturing - Aguirre-Cueva, Luis F; Alcantara-Gloria, Yasmin S; Cano Lazarte, Mercedes; Torres-Sifuentes, Carlos (LACCEI, 2023)
The food manufacturing sector in Peru is in constant growth and for 2019 it contemplated 25.20% according to the GDP by manufacturing activity, which represented 3.23% of the national GDP for that year. In our country, most manufacturing companies are classified as mypes, this is the case of the food sector, where more than 90% of the total industry are microenterprises. One of the main problems in these organizations is that the average efficiency level of a food industrial plant is 60%, however, according to studies it should not be less than 82%. In addition, as they are micro-enterprises, they do not have a very large budget to implement major changes or acquire technologically advanced machines that exceed their spending limit. That is why this research proposes the design of a productive management methodology to increase the level of efficiency of the production area of a Mype in the food industry through 5s and Poka Yoke tools. These Lean Manufacturing tools will contribute to the implementation of improvements at a low cost and quick understanding. The main purpose of this methodology is to increase the level of efficiency in the production area of organizations to improve the quality of the products and avoid waste that generates unnecessary expenses. In this way, it will contribute to increase the growth of GDP by manufacturing activity and therefore the national GDP. For the development of the methodology, Lean Manufacturing tools will be used, because the mypes seek to apply low-cost and easy-to-apply procedures.